Halal sustainable supplier selection using an integrated F-AHP and F-TOPSIS approach: A case study in the meat supply chain in Malang - Khoidir, Amelia; Bili, Ferderikus Ama; Rahmasari, Dewi (Journal of Halal Science and Research, 2025)
The halal meat supply chain faces unique challenges, including strict halal certification requirements, sustainability concerns, and the need for advanced traceability systems. Small and medium-sized enterprises (SMEs) frequently struggle to comply owing to financial and technological constraints. This study aims to construct a structured decision-making framework for selecting halal sustainable meat suppliers by combining the Fuzzy Analytical Hierarchy Process (F-AHP) and the Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (F-TOPSIS). F-AHP is used to define the evaluation criteria, build the hierarchical structure, and compute the relative weights using expert pairwise comparisons. Moreover, F-TOPSIS is used to evaluate suppliers, normalize the decision matrix, discover positive and negative ideal solutions, and compute the closeness coefficient to produce the final ranking. The results show that halal compliance is the most critical factor in supplier selection, with halal certification and product quality as the top priorities. The proposed framework provides a systematic approach to integrating halal and sustainability principles in supplier evaluation, supporting supply chain managers in making informed decisions while upholding worldwide halal and ecological requirements. Keywords: F-AHP, F-TOPSIS, Halal compliance, Halal sustainable supply chain, Meat industry, Supplier selection.